The Division of Gains from Complementarities in Human-Capital-Intensive Activity - Ethiraj, Sendil K.; Garg, Pranav (Organization Science, 2012)
This study uses data from the National Basketball Association to explore organizational mechanisms that affect the division of firm surplus in human-capital-intensive activity. It builds on the idea that reciprocal interdependence among team members creates the potential for complementarity. Complementarity, in turn, translates into higher firm surplus. The division of this surplus is subject to bargaining between the firm owner and labor. We argue that when complementarity increases, the firm owner's share of surplus will grow if interdependence among team members is symmetric. Furthermore, we identify three levers that make complementarity amenable to managerial design: the nature of interaction among team members, the relative dominance of team members, and the composition of a team. We find that greater interaction among team members and higher recruitment of team-oriented individuals are associated with increased complementarity, whereas dominant team members are associated with reduced complementarity. The study contributes to the literature on organization design by extending its implications to the division of surplus in human-capital-intensive activity.